Uso de la tierra y unidades productivas al finalizar el siglo XIX: Noroeste del Valle Central, Costa Rica - Samper Kutschbach, Mario (Revista de historia., 1986)
Studies the characteristics of land use toward the turn of the century in the province of Alajuela, Costa Rica, and especially in the northwestern part of Central Valley. Subregional differences are identified, as well as diffrences among varios types of productive units.